PENINGKATKAN PRESTASI BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN - Nurjannah, Nurjannah; Setiyadi, Desi (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
Mathematics learning achievement is still considered difficult by some students. This assumption arose because students did not understand what was learned, one of the materials was addition and subtraction of fractions. The purpose of this study is to improve mathematics learning achievement using the problem-based learning model of addition and subtraction of fractions. The research object was in class III SDN Labuan Barat with 26 students consisting of 12 male students and 14 female students. This type of research is Classroom Action Research. The instruments in this study used mathematical sum tests, observations, and field notes and documentation. Data analysis uses each cycle, namely 1) planning stage, 2) action stage, 3) observation stage, 4) reflection stage. Based on the results of the study showed that 1) cycle 1 got an average score of 76.54 with 73% of students completing, 2) cycle 2 got an average score of 94.85 with 89% of students completing and an increase of 18.31, it can be concluded problem-based learning models can improve learning achievement in the material of addition and subtraction of fractions in elementary schools